Point of View of University Scholars about Male-to-Female Gender Dysphorics in Pakistan - Haider, Syeda Kaniz-i- Fatima (Nurture, 2008)
The diversity within the gender identity of male-to-female gender dysphoric community is investigated with the goal of developing a model of gender identity that can more adequately describe this diversity than the current conceptualizations of gender identity disorders can do. Participants selected for the purpose were highly qualified teachers of Peshawar University. Participants completed an interviewbased questionnaire about their points of view and what contributed to their personal believes about gender dysphoria. Analysis of the data showed that even highly qualified teachers were not able to identify the difference between the types of gender dysphoria.